Предмет: Математика,
автор: mrzhilnov
Очень прошу решить, расписав всё как надо, пожалуйста
Приложения:
Ответы
Автор ответа:
0
Решение
1) a(2;2;-1) b(-2;3;2)
cosα = [2*(-2) + 2*3 + (-1)*2] / √(2² + 2² + 1)*√(4 + 3² + 2²) =
= (- 6 + 6)/(3*√17) = 0
cosα = 0
α = π/2
2) y = 2x⁵ - e^(2x)
y` = 10x⁴ - 2*e^(2x)
1) a(2;2;-1) b(-2;3;2)
cosα = [2*(-2) + 2*3 + (-1)*2] / √(2² + 2² + 1)*√(4 + 3² + 2²) =
= (- 6 + 6)/(3*√17) = 0
cosα = 0
α = π/2
2) y = 2x⁵ - e^(2x)
y` = 10x⁴ - 2*e^(2x)
Похожие вопросы
Предмет: Русский язык,
автор: medoffceba39
Предмет: Русский язык,
автор: sssdww
Предмет: Алгебра,
автор: olegarmas69
Предмет: Обществознание,
автор: ЛивМир
Предмет: Алгебра,
автор: shapar97